Coaching quality improvement in primary care to improve hypertension control. Issue 7 (17th July 2022) - Saunders, Emily; Teall, Alice M.; Zurmehly, Joyce; Bolen, Shari D.; Crane, Dushka; Wright, Jackson; Perzynski, Adam; Lever, Jonathan
ABSTRACT: Background: Effective management of hypertension (HTN) is a priority in primary care, necessary to decrease the costs, morbidity, and mortality associated with cardiovascular disease. Strategies to support quality improvement (QI) efforts in primary care are needed to make significant improvements in population health, especially for patients who experience socioeconomic inequalities. Local problem: To address the high rate (>50%) of uncontrolled HTN in the state of Ohio, a statewide QI project was implemented in high-volume Medicaid practices, aimed at improving blood pressure control and addressing racial disparities. The initiative expanded to include coaching QI to support efforts in primary care practices. Methods: The Model for Improvement guided development of Plan-Do-Study-Act (PDSA) cycles facilitated by QI coaching and APRN collaboration to implement key components of HTN guidelines: accurate blood pressure measurement, effective treatment, and timely follow-up. Interventions: Interventions were implemented after PDSA cycles over 18 months in two practice sites to address HTN control. Linking multiple PDSA test cycles and review of data bimonthly allowed for reflection on the impact of interventions for non-Hispanic Black patients and the overall patient population. Results: The percentage of patients with controlled HTN, repeat blood pressure measurement, and timely follow-up improved in an urban primary care practice associated with an academic medical center and in a rural federally qualified health center. Conclusions: Primary care practices can benefit from the external support of coaching when implementing QI processes to make meaningful change. APRNs are key collaborators for expanding QI efforts in primary care.